Respostas de espécies invasoras de Poaceae ao estresse hídrico, a competição com nativas filogeneticamente próximas e a mudança climática global. - Gonçalves, Larissa Carrara (2021)
Global climate change has as its main result an increase in the frequency and severity of extreme events, such as longer periods of drought, and more hot days throughout the year, which makes drought events even more severe. Certain plant species have a high invasive potential, which is due to their tolerance to adverse conditions and the recovery of their individuals after some disturbance, which increases the possibility of colonization and establishment in new environments, interfering with native communities. The effect of interspecific competition between the invasive plant Urochloa mutica and the native species Panicum dichotomiflorum was experimentally analyzed on its establishment, resistance and resilience, simulating conditions of extreme water events and the distribution of Panicum dichotomiflorum and Urochloa mutica, particularly in protected areas environmental. The results obtained showed that the native species grew less with the water changes, mainly due to the lack of water, and the invasive species did not show strong growth alterations with the disturbances used. Furthermore, the species were shown to alter the growth variables in competition, impacting the native species more. On the other hand, the species in terms of temporal stability did not change growth and both may have advantages in impacted environments. Regarding the distribution of species, the results showed that the dispersion of the invasive exotic plant will be greater in areas that already have its presence, and also that this species may invade new places, such as Germany and Austria. In a future scenario of global climate change in 2070, this invasive species could occur in protected areas. Regarding the national territory, U. mutica will lose part of its distribution in Brazil, mainly in the north and northeast regions, including areas of protection and conservation. For P. dichotomiflorum, it is possible that it will lose a large part of its natural habitat in the two future scenarios, but it will increase its occurrence in other places, being able to become a potential invasive. Therefore, the results achieved indicate that both species have important characteristics in coping with climate change and show that the native species has an invasive behavior, with information of enormous value to environmental managers, especially in the management work of the two species of Poaceae, which have invasive potential for preserved areas, and in research that evidence areas susceptible to invasion.